MENINGKATKAN LOYALITAS PELANGGAN RESTORAN MELALUI KUALITAS LAYANAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Soerjanto Soerjanto; Priyanto Priyanto; Nurti Rahayu (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
The purpose of this study is to determine whether customer loyalty, customer satisfaction, and restaurant service quality are positively correlated. In addition, research is being done on customer satisfaction as a mediator in the relationship between customer loyalty and service quality in restaurants. Purposive sampling was used to gather information from 300 patrons of fast-food restaurants using a questionnaire survey. Using Structural Equation Modeling with Partial Least Squares (SEM-PLS) in SMART PLS 3, the suggested model's hypotheses were investigated. The study's conclusions support the notion that customer loyalty, customer pleasure, and restaurant service quality are all positively correlated. However, the association between customer satisfaction and restaurant customer loyalty is not mediated by consumer satisfaction. This study emphasizes the significance of patron loyalty as a critical behavioral reaction in restaurants. The study's findings will help restaurant managers comprehend the vital significance that customer satisfaction and service quality play as marketing strategies to uphold and cultivate restaurant patron loyalty.